Factors Influencing Public Participation In Environmental Impact Assessment Process Of Nairobi-Thika Superhighway Improvement Project In Nairobi City County, Kenya - Owiny, Patrick; Agwata, Jones; Muguia, Kariuki (Machakos University Press, 2021)
Public participation is a key component in environmental impact assessment and governance. Public participation is a process by which public concerns, needs and values are incorporated into governmental and corporate decision-making with the overall goal being decisions that are supported by the public. Public participation is also important in the development and management of natural resources. Environmental impact assessment (EIA), on the other hand, is a procedure which seeks to ensure that adequate prior information is obtained on likely environmental consequences of development projects, on possible alternatives and on measures to mitigate the adverse impacts. The objective of this study was to examine key factors influencing public participation in the EIA process for the Nairobi-Thika Superhighway Improvement Project in Nairobi City County. The study adopted a descriptive research method with a total sample of 120 respondents/households sampled from along the Nairobi-Thika Superhighway within the County. The key finding of the study is that despite high levels of public awareness about t project, there was low knowledge on the need to participate and low level of actual participation in the EIA process. The reasons for low participation were attributed to lack of time, lack of knowledge about the need for participation and lack of trust and transparency in the EIA process. The study recommends enhancement of public education about public participation in development projects. Project planners and implementers need to observe transparency in the EIA process for increased public trust, acceptability and support.
Keywords: Public Participation; Environmental Impact Assessment; Public Education; Transparency; Trust; Acceptability